Nine questions on energy decomposition analysis. Issue 26 (28th June 2019) - Andrés, Juan; Ayers, Paul W.; Boto, Roberto A.; Carbó‐Dorca, Ramon; Chermette, Henry; Cioslowski, Jerzy; Contreras‐García, Julia; Cooper, David L.; Frenking, Gernot; Gatti, Carlo; Heidar‐Zadeh, Farnaz; Joubert, Laurent; et al.
Abstract : The paper collects the answers of the authors to the following questions: Is the lack of precision in the definition of many chemical concepts one of the reasons for the coexistence of many partition schemes? Does the adoption of a given partition scheme imply a set of more precise definitions of the underlying chemical concepts? How can one use the results of a partition scheme to improve the clarity of definitions of concepts? Are partition schemes subject to scientific Darwinism? If so, what is the influence of a community's sociological pressure in the "natural selection" process? To what extent does/can/should investigated systems influence the choice of a particular partition scheme? Do we need more focused chemical validation of Energy Decomposition Analysis (EDA) methodology and descriptors/terms in general? Is there any interest in developing common benchmarks and test sets for cross‐validation of methods? Is it possible to contemplate a unified partition scheme (let us call it the "standard model" of partitioning), that is proper for all applications in chemistry, in the foreseeable future or even in principle? In the end, science is about experiments and the real world. Can one, therefore, use any experiment or experimental data be used to favor one partition scheme over another? © 2019 Wiley Periodicals, Inc. Abstract : Many methods enable the calculation of contributions to the interaction energy between two fragments of a molecular or complex system.